HIGH-FREQUENCY ATTENUATION IN THE CRUST AND UPPER MANTLE OF THE NORTHERN TIEN SHAN - Martynov V.G.; Vernon F.L.; Mellors R.J.; Pavlis G.L. (My University, 1999)
We analyze 243 three-component broadband digital seismograms of aftershocks from the Ms. = 7.3 Suusamyr, Kyrgyzstan, earthquake to determine seismic attenuation in the northern Tien Shan. Pg, Sg, and SmS body waves and S coda waves were used to estimate the frequency-dependent (f = 1.2-30 Hz) attenuation and scattering parameters of the crust and upper mantle as a function of depth. Using the equation Q(f) = Q0fn for multiple layers, we find that Q0 increases with depth from 76 (upper crust) to 1072 (upper mantle), and the value of n decreases from 0.99 to 0.29 over the same range. The Q coda results also demonstrated an azimuthal dependence: Q0 = 736 in the north-south direction and Q0 = 494 in the east-west direction. There is a strong 2φ dependence on azimuth for high frequencies (>1.2 Hz). The depth and azimuthal dependence of the quality factor show that the Q is complicated and three dimensional. Estimates of the inhomogeneity scale a show two types of multiple scatterers (Wu and Aki, 1985): a velocity perturbation with a = 0.5-3.0 km and an impedance perturbation with a = 0.052-0.413 km. It appears that a increases with depth. The coefficient of scattering decreases from 〈g0〉f = 0.0055 km-1 at h = 0-6 km to 0.0020 km-1 at h = 6-11 km and 0.0048 km-1 at h = 11-15 for forward scattering and 〈gπ〉f = 0.0006 km-1 at depth of low crust and upper mantle for backscattering. Estimates of seismic albedo B0 show that the primary source of attenuation is intrinsic anelasticity, and the variation of Q0 and n indicates that the level of heterogeneity varies with depth, possibly due to pressure. The lateral variation of Q0 can be connected with azimuthal anisotropy in the upper mantle related to current deformation under the Tien Shan.